ANALISIS RASIO SOLVABILITAS PADA PERBANKAN SYARIAH YANG TERDAFTAR DI JII70 - Faizah, Iva; Tahir, Muhammad (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
The increase in company debt will be inversely proportional to the increase in profits, the higher the company's debt, the lower the profit obtained, but the increase in debt is precisely in line with the increase in profits. This article looks at the development of financial performance of Islamic financial institutions that become public companies using solvency ratio measurement indicators. Quantitative methods with secondary data in the form of financial statements that are the main data source. Data analysis shows that the level of financial solvency shows good conditions at 35%. BTPN Syariah showed poor condition because the ratio was above the industry standard of 35%. The implication for other similar banks is that it is important to maintain the stability of solvency ratios to remain below industry standards to prevent companies from the risk of default in paying debt.